Implementasi Program Bantuan Pangan Non Tunai di Kecamatan Warudoyong Kota Sukabumi - Yuniarti, Ratu; Mulyadi, Andi; Sampurna, Rizki Hegia (UNIVERSITAS ISLAM SYEKH YUSUF, 2023)
Non-Cash Food Assistance is a policy program created by the government with the aim of helping people meet their food needs. This study aims to determine the implementation of the Non-Cash Food Assistance program in Warudoyong District, Sukabumi City. In this study, researchers used qualitative research methods with a descriptive approach with informants consisting of 5 people who were determined by purposive sampling technique. The data collection techniques in this study used interview techniques, observation and documentation as well as the data validation process was carried out using technique and source triangulation. The results of this study indicate that the implementation of the BPNT program in Warudoyong District, Sukabumi City, is assessed from the four indicators of accuracy based on Richard Matland's theory that it has gone quite well, because the policy program has been able to help the community in accordance with program objectives, besides that in practice the implementing actors have carried out their duties and roles are in accordance with the BPNT General Guidelines, the policy target is that KPM has met the requirements and criteria for receiving non-cash assistance, then the relationship between policy implementers and the community is going well through outreach and education related to policy programs.